Correction: Neonatal Resuscitation and Adaptation Score vs Apgar: newborn assessment and predictive ability. (November 2018) - Witcher, Teresa; Jurdi, Shadi; Kumar, Vidhya; Gupta, Aditi; Moores, Russell; Khoury, Joseph; Rozycki, Henry
Since the publication of the above article, the authors have noted that the name of the first Item in the NRAS scoring system in Figure 1 was omitted. It is Heart Rate (C1). The authors apologise for any inconvenience caused by this error. The html and online pdf versions have now been rectified and carry the corrected Figure.